2013
DOI: 10.5271/sjweh.3345
|View full text |Cite
|
Sign up to set email alerts
|

Disability pension due to musculoskeletal diagnoses: importance of work-related factors in a prospective cohort study of Finnish twins

Abstract: Several work-related risk factors, such as physical workload and stress, are independent, direct risk factors for disability pension due to musculoskeletal diagnosis, not affected by familial factors. Identification of these risk factors during a person's lifespan would be beneficial for occupational health care and individuals to reduce permanent work incapacity due to musculoskeletal diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…Various kinds of working conditions have been shown to be risk factors for DR (17)(18). In previous studies, a high physical workload, low job control, and chemical and physical exposures at work have provided the largest contributions to socioeconomic differences in DR due to MSD (2, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of working conditions have been shown to be risk factors for DR (17)(18). In previous studies, a high physical workload, low job control, and chemical and physical exposures at work have provided the largest contributions to socioeconomic differences in DR due to MSD (2, 4).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prospective epidemiological evidence from a twin study in Sweden reported statistically significant excess risk of obtaining disability pension due to MSD among workers employed in the health care and social sector, transport, production and mining, services and military [12]. Concerning physical risk factors, another prospective twin study in Finland confirmed that shift work, monotonous work, lifting and carrying, physically demanding work are strongly associated with work incapacity and disability pension [13]. The results of both studies were consistent after controlling for genetic and shared-environment factors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Finnish study found that unemployment, changes of workplace and negative factors related to the work environment were all strong risk factors for DP based on musculoskeletal diagnoses, even when social background factors were taken into account 22. Another Finnish study, which used a composite index for core–periphery position, based on work hours, employment permanency and unemployment income, found associations with self-rated health, diagnosed diseases and depression, even among the less disadvantaged positions on the core–periphery scale 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that unemployment experience is associated with an increased probability of being granted a DP,1922 but findings on the more intermediate positions are scarce.…”
Section: Introductionmentioning
confidence: 99%